CRITICISM OF THE ISLAMIC INHERITANCE DISTRIBUTION SYSTEM PERSPECTIVE OF THE PRINCIPLE OF PROPORTIONALITY. - Nor Salam (MAQASHID Jurnal Hukum Islam, 2023)
This paper is motivated by the debate about the existence of inheritance law in Islam which is often stigmatized as a law that is not friendly to the element of equality in the percentage of acquisition of men and women. This background will then be examined in this paper by proposing a perspective on the principle of proportionality as the basis of Islamic inheritance law. Through a normative-doctrinaire legal study method, this study concludes that the principles of inheritance are eclectic between the principle of proportionality and the principle of justice. This has implications for social decency, which can be between different time and period dimensions or between one community and another that has different standards.